Presenting the model of factors affecting the resilience of entrepreneurial behavior in Technical and Vocational University of Alborz province - Ali Abdi Jamayran; Manouchehr Niknam; Hasan Rangriz (مدیریت و چشم انداز آموزش)
The purpose of this research is to provide a model of factors affecting the resilience of entrepreneurial behavior in Alborz Technical and Vocational University. According to its purpose, the research method is applicable, and in terms of implementation, it is qualitative, of thematic analysis type. The statistical population of the research includes 12 participants who are experts and professors of entrepreneurship. Sampling was done in a purposeful and snowball way. A semi-structured interview was used to collect information and the interviews continued until reaching theoretical saturation. For analysis, open and axial and selective coding through MAXQDA software was used. The results of the research showed that the central phenomenon of the resilience of entrepreneurial behavior in the university has four dimensions: environmental drivers, development factors, environmental barriers, and limiting factors. Financial and legal strategy, operational strategy, international strategy, and policy making strategy is needed to increase the resilience of entrepreneurial behavior in the university, which leads to economic, scientific and cultural consequences at the level of the country. Financial and economic fields, appropriate support and policies in a changing environment, and an intense competitive environment help the resilience strategies of entrepreneurial behavior in the university to be operationalized under suitable situation. In this field, there are scientific, human, managerial, legal, structural, and financial obstacles that, by identifying and solving them, the improvement of the resilience dimensions of entrepreneurial behavior in the university and basic strategies can be maintained.Extended abstractIntroductionThe modern era is associated with a dynamic and complex environment and extensive changes in the scientific, economic, and social fields; and the business environment is constantly changing and full of risk (Chitsazan et al, 2018). Meanwhile, change management to adapt to an uncertain future, as an important challenge, requires basic infrastructures (Talari et al, 2021). In this regard, communication and information, as well as human power and their intellectual resources are the most important factors of competitive advantage in this situation. Undoubtedly, entrepreneurs are important in the economic development of countries by using creativity and internal initiative. Entrepreneurship is an interdisciplinary topic discussed in various fields such as psychology, sociology, economics, and management (Ebrahimi, 2018). Although entrepreneurs are known as people who are enthusiastic and interested in their jobs, they are always exposed to negative emotional states such as anxiety, fear and stress which, in turn, affects their entrepreneurship and opportunity recognition, decision-making, and creativity (Bulmash, 2016). This indicates that entrepreneurs face many threats and obstacles in the path of job creation. These obstacles cause disruption (Ghanbari et al, 2017) and ultimately accelerate entrepreneurial failure. This is a point that considers the individual resilience of the entrepreneur to be important in facing these factors (Vermziari & Imani, 2018). Resilience is one of the personality traits of entrepreneurs, and it is known as emotional and cognitive ability for entrepreneurs. Also, it is the driver of entrepreneurial performance or success that helps the entrepreneur to resist internal and external shocks. Entrepreneurial resilience refers to the ability of entrepreneurs to continue their future plans despite unstable events, market problems, and life conditions. This feature enables entrepreneurs to reduce the harmful effects of unexpected events, overcome it, and search for better situations (Fatoki, 2018). Theoretically, entrepreneurial resilience is related to the psychological trait theory based on the entrepreneur's personality traits and the attribution theory. Trait theory argues that entrepreneurs have their own personality traits, and entrepreneurial resilience is also dependent on personality traits. According to the attribution theory, entrepreneurial success or failure can be attributed to three dimensions. These items are the source of causality, stability, and controllability. Entrepreneurs may evaluate the outcome of events within or outside of their personal control. They attribute the tendency to succeed as well as not to succeed only to themselves and their actions (Rezai Moghadam & Masoumi, 2018).Therefore, the current research seeks to answer the question: what is the model of factors affecting the resilience of entrepreneurial behavior in Alborz Technical and Vocational University?Theoretical FrameworkEntrepreneurshipOrganizational entrepreneurship can be developed by delegating responsibility to employees to prepare budgets appropriate to their tasks, or by managing their departments as independent self-governing units (Cantino et al, 2017). Organizational entrepreneurship focuses on initiative and entrepreneurial spirit. An executive with an entrepreneurial spirit behaves as if he owns the company. This spirit leads to the desire to take more risks, understand how the market works, get rid of bureaucratic diseases, desire to do innovative activities, and emotional commitment to the organization (Davali et al, 2022).ResilienceResilience is one of the main structures of the positive psychology approach. In recent years, this approach with the slogan of paying attention to human talents and abilities (instead of dealing with disorders and anomalies) has been noticed by researchers, and includes different concepts. Resilience in the word means having a springy state and a reversible state; and in the psychological sense, it explains how people deal with unexpected situations and show stubbornness in the face of stress and unfortunate conditions. (Arce & Hitchcock, 2019).Zare davijani et al, (2023) investigated the identification of factors affecting the weakening of entrepreneurship in university graduates of Payam Noor universities in Tehran province. The output of the research is to emphasize the strengthening of four variables, including the individual and personal capabilities and qualifications of the graduates, strengthening the educational elements related to the development of entrepreneurship in the university, strengthening the government's support conditions (facilitation, support, and encouragement), and finally intervention in the six environments effective on university entrepreneurship.Heydary et al, (2023) studied the design of a model of resilience in government organizations of Kermanshah province. The results indicate that the causal factors include; Individual, group, and organizational factors. Also, the environment platform includes; the role of the government, political and economic factors, and electronic platforms. The consequences also indicate the continuity and progress of the organization. The results of the structural equations also showed that the resilience model has a favorable fit in government organizations.Research methodologyAccording to its purpose, the research method is applicable, and in terms of implementation, it is qualitative, of thematic analysis type. The statistical population of the research includes 12 participants who are experts and professors of entrepreneurship. Sampling was done in a purposeful and snowball way. A semi-structured interview was used to collect information and the interviews continued until reaching theoretical saturation.Research findingsFor analysis, open and axial and selective coding through MAXQDA software was used. The results of the research showed that the central phenomenon of the resilience of entrepreneurial behavior in the university has four dimensions: environmental drivers, development factors, environmental barriers, and limiting factors. Financial and legal strategy, operational strategy, international strategy, and policy making strategy is needed to increase the resilience of entrepreneurial behavior in the university, which leads to economic, scientific and cultural consequences at the level of the country. Financial and economic fields, appropriate support and policies in a changing environment, and an intense competitive environment help the resilience strategies of entrepreneurial behavior in the university to be operationalized under suitable situation. In this field, there are scientific, human, managerial, legal, structural, and financial obstacles that, by identifying and solving them, the improvement of the resilience dimensions of entrepreneurial behavior in the university and basic strategies can be maintained.ConclusionThe current research has been conducted with the aim of providing a model of factors affecting the resilience of entrepreneurial behavior in Technical and Vocational University of Alborz province. The results of this research is in agreement with the results of Zare davijani et al, (2023), Heydary et al, (2023), Karimi et al, (2022), Fernandez et al, (2022), Buruj Ali (2022), Khodaparast et al, (2022), Tabares et al, (2021), Nazari et al, (2020), Badzaban et al, (2020), Towers et al, (2020), Hasani et al, (2019), Al-Haddad et al, (2019), and Osborne & Gaebler (2018). Fernandez et al, (2022) examined entrepreneurial resilience: a case study on university students. The results show that resilience is built through intrapersonal and extrapersonal processes. These processes form a set of strategic dimensions related to entrepreneurial behavior applied to build personal projects.According to the results of the research, the following suggestions were presented:For the financial and legal strategy; solutions such as awareness of national and regional laws, taking advantage of protective laws, adapting laws and regulations, and budgetary and financial support are suggested. For the operational strategy; solutions such as research prioritization, entrepreneurship education planning, creation of science and technology parks, creation of growth centers, creation of learning network, creation of multinational companies and institutions, creation of technology transfer networks, creation of regional and international academic entrepreneurship networks, creation of industry and university liaison offices, creation of government and university networks, creation of entrepreneurial networks and institutional cooperation between them, educational and research and innovation institutions.